The COVID-19 pandemic and its impacts on sub-urban society in Yogyakarta, Indonesia: A qualitative study - Bayu Fandhi Achmad; Shalmannuary Nisya Allquarismy; Siska Pratiwi; Yohannes Aruna Kertiyasa; Dewanggani Kirana; Dhyanti Mutiasari; Vineshankar Ravichandar; Yosafat Budiharjo Santoso Simanungkalit; Dionisia Setya; Farah Nabila Firry; Syaiful Ghozali; Wahida Yuyun Suciati (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2021)
Indonesia is the country which has the most COVID-19 cases in South East Asia. The COVID-19 pandemic is causing serious psychological, social, and economic impacts particularly on the sub-urban society. This study aimed to explore the impacts of the COVID-19 pandemic on sub-urban society in Yogyakarta, Indonesia. This study used a hermeneutics phenomenological approach. that enrolled seven participants who reside in the sub-urban area of Yogyakarta province in June 2020. Semi-structured interviews were conducted with participants through Whatsapp mobile application and analyzed using interpretive phenomenological methods. Results showed that the impact of the COVID-19 pandemic can be summarized into three themes. First, the impacts include negative emotions that arise due to psychosomatic symptoms, fear of losing loved ones, stereotypes and anxiety concerning contracting COVID-19 infection; Second, limited social interaction in the community and strict travel restrictions; and third, job and income losses including layoffs from work and fear of not being able to meet family basic needs. The COVID-19 pandemic is causing several serious impacts involving psychological, social, and economic concerns that are disrupting the sub-urban society. Individual coping and family support are needed in the current situation.